THE ROLES OF TECHNOLOGY ACCEPTANCE, USER CREDIBILITY AND COVID-19 PERCEIVED HEALTH RISK IN TOURIST’S SOCIAL MEDIA USER-GENERATED-CONTENT USAGE INTENTION - Hanafiah, Mohd Hafiz; Zain, Adilah Md; Asyraf, Muhammad Aliff; Makhasi, Ghifari Yuristiadhi Masyhari (2022)
This study examines the direct effects of technology acceptance (perceived usefulness and ease of use), trustworthiness, expertise, and the moderating effect of COVID-19 perceived health risk on tourists’ social media User-Generated-Content (UGC) usage intention. The study respondent was 233 Malaysian tourists who travelled domestically for leisure during the COVID-19 pandemic. The study hypotheses were examined using multiple regression analysis. The hypotheses testing indicates that perceived usefulness, ease of use, trustworthiness, and expertise significantly affect future usage of social media UGC. In addition, the findings confirm that perceived health risk does not affect the user trustworthiness and future usage of social media UGC. The findings assist tourism stakeholders in understanding tourist behaviour towards social media UGC, especially during the COVID-19 pandemic. The tourism business and policymakers should continuously improve and monitor their UGC platform, especially since UGC was deemed one of the vital information dissemination channels during the COVID-19 pandemic. © 2022, Universidad de Huelva. All rights reserved.